Contributory Factors for Teen Insomnia Symptoms: A Prospective Cohort Study in Sweden - Hedin, Gita; Norell-Clarke, Annika; Tønnesen, Hanne; Westergren, Albert; Garmy, Pernilla (Frontiers in Neuroscience, 2022)
Objectives: Insufficient sleep is a public health problem that impacts the mental and physical health of children and adolescents. Complaints of insomnia are particularly pervasive among adolescents. This longitudinal study investigates factors that contribute to teen insomnia symptoms. Design: 5-year prospective follow-up study. Setting: School-based. Participants: 522 children (49.8% girls) aged 9.4 ± 1.3 years at baseline; 14.4 ± 0.7 years at follow-up. Intervention: Not applicable. Measurements: The dependent variable of insomnia symptoms at follow-up was assessed with the Minimal Insomnia Symptom Scale – Revised. The independent variables at baseline were the perceived family financial situation, tiredness at school, problems waking up, short sleep duration, sleeping difficulties, having a bedroom TV, and time spent with a TV/computer. Multivariate binary logistic regression analyses were used to examine whether the independent variables at baseline predicted insomnia symptoms at follow-up. Results: Perceived quite bad/very bad family financial situation (OR 3.1; CI 1.4-6.7) and short sleep duration (< 10 hours) (OR 2.3; CI 1.0-5.3) among girls at baseline were associated with insomnia symptoms at follow-up. Having problems waking up among boys at baseline was associated with insomnia symptoms at follow-up (OR 4.9; CI 1.6-14.4). Conclusions: Short sleep duration, problems waking up, and perceived bad family financial situation during childhood were linked with adolescent insomnia symptoms. The sex-based differences in these associations warrant further investigation to effectively mitigate adolescent insomnia.